2017
DOI: 10.1097/qco.0000000000000351
|View full text |Cite
|
Sign up to set email alerts
|

Duration of pneumonia therapy and the role of biomarkers

Abstract: Shortening the duration of antibiotic regimens in pneumonia seems a reasonable strategy for reducing selective pressure driving antimicrobial resistance and costs provided that clinical cure is guaranteed. Procalcitonin-based protocols have been proven essentially helpful in this direction. VIDEO ABSTRACT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…Although far from being ideal, PCT is one of the most well-studied biomarkers in RCTs including over 7000 patients suffering with all types of LRTIs, at all treatment settings. It has been proved to have a more favourable kinetic profile and to be more sensitive and specific than other biomarkers, such as IL-6, C reactive protein (CRP) and lactate 31,32 ; it demonstrates a mean sensitivity of 94.1% and specificity of 88.4% for the diagnosis of LRTIs 33 with a negative predictive value to rule out LRTIs to be Figure 1. The physiological pathway of calcitonin (CT) takes place in the thyroid C cells.…”
Section: Diagnostic Value Of Procalcitoninmentioning
confidence: 99%
See 2 more Smart Citations
“…Although far from being ideal, PCT is one of the most well-studied biomarkers in RCTs including over 7000 patients suffering with all types of LRTIs, at all treatment settings. It has been proved to have a more favourable kinetic profile and to be more sensitive and specific than other biomarkers, such as IL-6, C reactive protein (CRP) and lactate 31,32 ; it demonstrates a mean sensitivity of 94.1% and specificity of 88.4% for the diagnosis of LRTIs 33 with a negative predictive value to rule out LRTIs to be Figure 1. The physiological pathway of calcitonin (CT) takes place in the thyroid C cells.…”
Section: Diagnostic Value Of Procalcitoninmentioning
confidence: 99%
“…Even though the use of PCT in guiding antibiotic initiation may be disputed, it is successfully assessed as part of antibiotic discontinuation protocols 32 . Zhang et al 54 (2015) reviewed 43 antibiotic stewardship programs (ASPs) related studies, in eight of which PCT-guided antibiotic protocols were used 54 .…”
Section: Prognostic Value Of Procalcitoninmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies and reviews have supported shorter duration of antibiotic therapy in patients with CAP and suggested that the use of biomarkers, such as PCT, may be useful in guiding both the initiation and the duration of antibiotic treatment 48 , 49 . One group of investigators documented that an implementation strategy, tailored to identify previous barriers to early switch, was associated with a reduced duration of intravenous therapy 50 .…”
Section: Antibiotic Treatment Of Community-acquired Pneumoniamentioning
confidence: 99%
“…В последнее время с целью определения оптимальной длительности АБТ внебольничных инфекций нижних дыхательных путей, в т. ч. и ВП, наряду с учетом динамики соответствующих клинических симптомов заболевания, стали использоваться и биомаркеры (прежде всего прокальцитонин -ПКТ) [51]. При этом разработан своеобразный алгоритм, ориентируясь на который, врачу предлагается либо продолжить лечение, либо прекратить дальнейшее назначение антибиотиков (рис.…”
Section: биомаркеры и длительность антибактериальной терапии больных unclassified